Improving the design of an open auditorium: On the relationship between flow dynamics and building arrangement. (January 2021) - Rodrigues, V.; Vicente, B.; Sorte, S.; Rafael, S.; Oliveira, K.; Silva, S.; Miranda, A.I.; Borrego, C.
Graphical abstract: Highlights: Building arrangement has a strong impact on the turbulent flow dynamics. Flow dynamics patterns confirm the citizens' perception of wind discomfort. Highest wind speeds are recorded within the auditorium. Countermeasures are effective in improving comfort of the built environment. Need for regulations concerning pedestrian wind comfort criteria. Abstract: The complexity of the built environment plays an essential role on the local urban microclimate. Therefore, this work aims to assess the impact of buildings arrangement on the overall turbulent flow dynamics. This study is conducted for the neighborhood of an open auditorium located in an urban area. A set of experiments were accomplished using a wind tunnel, together with a set of Computational Fluid Dynamics (CFD) simulations. Both the experiments and the CFD simulations were carried out for a set of meteorological conditions identified as prevailing in the auditorium area. The physical and numerical approaches were used to assess the wind patterns for the reference scenario. Furthermore, a series of mitigation measures was simulated to evaluate their effectiveness in reducing the wind speed at pedestrian level in the neighborhood. The overall results emphasize the role of the mitigation measures to reduce wind speed and potentially improve pedestrian wind comfort levels in the auditorium. The originality of this paper relies on the design and test of the set of proposed mitigation measures, through the combination of complementary tools, as well as the expertise of distinct practitioners, and their insights regarding their effectiveness.